Unpacking climate services: Knowledge politics, beneficent humanitarianism and the realpolitik of risk management in China. (August 2022) - Nobert, Sebastien; Wen, Cheng
Abstract: In the last four decades, climate services (CS) have moved from being limited forecasting tools in their predictive capacity to becoming involved in the shaping of risk assessment instruments with global reach affected to enhance adaptation to climate change. Yet, they have been relatively overlooked by human geographers and critical risk theorists, whose interests have been to document the political processes involved in shaping climate change and the global scientific enterprise it has generated. By looking at the ways in which CS have been developed and exported to countries deemed as climate-vulnerable, the paper sheds light on two simultaneous kinds of knowledge politics that are occurring at the interstices of global human security aspirations and the realpolitik of local practices. The first emerges from the ways in which CS political relevance has been secured by climate scientists in the midst of grand developmentalist and humanitarian ambitions, what we have called beneficent knowledge politics. The second comes from the nitty-gritty of risk management practices in countries to which CS are exported, in this case China, and highlights how a myriad of knowledge and sensitivities involved in shaping risk and science have been overlooked by the superseding ideals underpinning the production of CS and their application to wider climate adaptation agenda. By doing so, the paper contributes to the geographies of risk and emergencies as well as to the geographies of science by enhancing our understanding of the knowledge politics at play in the development of and resistance to technocratic climate governance.